Microbial Communities and Nitrogen Transformation in Constructed Wetlands Treating Stormwater Runoff - Shirdashtzadeh, Maryam; Chua, Lloyd H. C.; Brau, Lambert (Frontiers in Water, 2022)
Microbial communities play a vital role in nitrogen (N) removal in constructed wetlands (CWs). However, the lack of studies on microbial characteristics of wetland systems designed to treat stormwater demonstrates the importance of comprehensive investigation on microbial response to wetland fluctuations. Moreover, the observed inconsistency in N removal, and detected links between microbial shifts and wetland water level fluctuations is an area of research interest perculiar to stormwater applications. This study surveyed nearly 150 publications to provide a summary and evaluation of N removal efficiency in different types of CWs where microbial communities and their behavior have been correlated to regulating factors. Factors such as flow regime, plants, and physico-chemical properties (e.g., temperature, dissolved oxygen, pH, and nitrogen concentration) were found to significantly influence microbial diversity and composition. Although many studies have analyzed microbial N removal, a majority conducted their studies in bioretention systems. Accordingly, some of the microbial pathways in CWs designed for stormwater treatment have not been investigated. As such, it is suggested that pathways, such as dissimilatory nitrate reduction to ammonium (DNRA) and comammox activity and their changes over dry-wet cycles in stormwater constructed wetlands be investigated. This information could assist engineers to take advantage of the presence of other N transforming communities which could improve microbial diversity within wetland systems. Moreover, it is recommended to track microbial functional genes and their changes over wetland water fluctuation to develop an ecosystem with conditions favorable for microbial pathways with higher N removal potential. In conclusion, the findings of the current literature review reinforce the importance of stormwater runoff treatment and the implementation of new design strategies that are able to enhance microbial activity and diversity leading to a better treatment outcome.